Halal Certification in Supporting the Growth of Halal MSMEs (Case Study of the Sidikalang Coffee Industry) - Lailya Kurniati Limbong; , Sugianto; , Atika (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study analyzes the role of halal certification in supporting the growth of halal MSMEs, with a case study on the coffee industry in Sidikalang. Indonesia has great potential for the halal industry due to its large Muslim population and increasing consumer awareness. Halal certification is strategic for MSMEs because it can increase competitiveness, build consumer trust, and open access to a wider supply chain. This study uses a qualitative approach through case studies, in-depth interviews with four coffee SME actors, and secondary data from policy documents, reports, and scientific articles. The results show that SMEs' understanding of halal certification is still low due to assumptions about natural raw materials, the application process being considered complicated, lengthy, and expensive, and a lack of socialization from the government. However, SMEs that have certification have experienced an increase in sales, market share, and consumer trust. Collaboration between the government, relevant agencies, and educational institutions is needed to promote inclusive halal certification, especially in non-urban areas.